Metode Penelitian Tindakan Kelas: Konsep, Tahapan dan Keunggulan dalam Praktik Pembelajaran - Ade Rahayu; Arna Saskia (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study aims to examine in depth the consepts, stages, and adventages of the Classroom Action Reseacrh (CAR) method as an effective approach to improving the quality of learning in schools. The research method employed ia a literature review, involving the collection ans analysis of various scholarly sources such as journals, books and relevant research findings. The result indicate that CAR is a form of reaerch that can be conducted by teachers in their own classroom through a cyclical process consisting of planning, action implementation, observation, and reflection. This cycle enables teachers to continuously improve their teaching approaches and strategies. Findings from the reviewed literature highlight the strengths of CAR, which not only enhances student learning outcomes but also contributes to the professional development of teachers. Teachers are encouraged to think reflectively and creatively, with a strong focus on improving the quality and process of instruction. Classroom Action Research holds strategic value in fostering innovative, creative, and collaborative learning practices that positively impact both student achievement and teachers’ instructional performance.